Analysis and Development Social Media Marketing Effectiveness on Cleaning Service Among Customer in Batam City - Diny Anggriaini Adnas; Wisely Liang (STMIK Banjarbaru, 2023)
The digitalization era has become an era that is a source of information for the community. Entrepreneurs can promote their business through social media to get the attention of potential customers. The meaning of this research is to show whether social media marketing can help marketing cleaning services in the city of Batam. The research population is 420 respondents who are residents of the city of Batam. Research data has been collected by random sampling technique. There are 28 data outliers that have been detected through the SPSS application and deleted from the study, so that the total research data is 392 samples. The results of the study show that Brand Trust and Brand Equity have a significant effect on Brand Loyalty. If you increase Brand Trust and Brand Equity, consumers will be more interested in subscribing to the business.Keywords: Brand trust; Brand loyalty; Brand equity; Digitization; social media AbstrakEra digitalisasi telah menjadi era yang bersifat sumber informatif bagi masyarakat. Pengusaha dapat mempromosikan usaha melalui sosial media untuk mendapatkan perhatian calon konsumen. Makna penelitian ini adalah menujukkan apakah sosial media marketing dapat membantu pemasaran jasa kebersihan di kota Batam. Populasi penelitian adalah 420 responden yang merupakan penduduk kota Batam. Data penelitian telah dikumpulkan dengan teknik random sampling. Terdapat 28 data outlier yang telah terdeteksi melalui aplikasi SPSS dan dihapus dari penelitian, sehingga jumlah data penelitian sebanyak 392 sampel. Hasil penelitian menunjukkan bahwa Brand Trust dan Brand Equity berpengaruh signifikan terhadap Brand Loyalty. Jika Meningkatkan Brand Trust dan Brand Equity maka konsumen akan lebih tertarik untuk berlanggan di bisnis tersebut.